Mediating Effect of Organizational Virtuousness in Relationship between Ethical Leadership and Knowledge Hiding: Evidence from Higher Educational Institutions of Punjab, Pakistan - Muhammad Asadullah; Dr. Khalid Rehman (Corresponding Author); Dr. Nafid Khan; Dr. Rafiullah; Dr. Shumaila Hashim; Sadiq Ullah (Al-Qanṭara, 2023)
Purpose: This study aimed to examine the impact of ethical leadership on the knowledge-hiding behavior of university faculty members, considering the mediating role of organizational virtuousness. Design/Methodology/Approach: Respondents for this study were randomly selected from 327 faculty members employed at universities in the Punjab province of Pakistan, established before the year 2015. Using a cross-sectional design, the principal author administered a questionnaire measuring ethical leadership, organizational virtuousness, and knowledge hiding. Findings: The study revealed that ethical leadership and organizational virtuousness can predict knowledge hiding. Additionally, ethical leadership had a significant indirect effect and an insignificant direct effect on knowledge hiding in the presence of organizational virtuousness, thereby proving full mediation. Research Limitations/Implications: While the findings are insightful, it is essential to acknowledge certain limitations in the study. These limitations can guide future research in this domain, offering avenues for further exploration and refinement. Practical Implications: The study’s outcomes have practical implications for organizational leaders, suggesting that fostering ethical leadership and organizational virtuousness can mitigate knowledge-hiding behaviors among faculty members. Originality/Value: Contrary to common beliefs, this study supports the assumption that the effect of ethical leadership on knowledge hiding is mediated through organizational virtuousness. This novel insight contributes to the existing literature and underscores the importance of ethical leadership and virtuous organizational practices.